2015
DOI: 10.1097/mnm.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

The value of fluorine-18 fluorodeoxyglucose PET/MRI in the diagnosis of head and neck carcinoma

Abstract: 18F-FDG PET/MRI demonstrated high sensitivity and moderate specificity in the diagnosis of head and neck carcinoma lesions. 18F-FDG PET/MRI is an accurate method in the diagnosis of head and neck carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…29,47,48 Even if it concerned both sequential and simultaneous FDG-PET/MRI studies, Xiao et al showed in a recent meta-analysis a pooled sensitivity of 91% to detect head and neck cancer. 49 To strengthen our view, Schaarschmidt et al recently showed in a series, including a majority of small size lesions (10/12), a higher sensitivity of FDG-PET/MRI (Se 5 75%) than FDG-PET/CT (sensitivity 5 59%, P 5 .06) and MRI (sensitivity 5 50%, P 5 .03) in detecting primary tumors. 50 This study suffered from several limitations.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…29,47,48 Even if it concerned both sequential and simultaneous FDG-PET/MRI studies, Xiao et al showed in a recent meta-analysis a pooled sensitivity of 91% to detect head and neck cancer. 49 To strengthen our view, Schaarschmidt et al recently showed in a series, including a majority of small size lesions (10/12), a higher sensitivity of FDG-PET/MRI (Se 5 75%) than FDG-PET/CT (sensitivity 5 59%, P 5 .06) and MRI (sensitivity 5 50%, P 5 .03) in detecting primary tumors. 50 This study suffered from several limitations.…”
Section: Discussionsupporting
confidence: 57%
“…To date, the first published series comparing FDG‐PET/CT and FDG‐PET/MRI performances in HSNCC staging reported no significant difference in accuracy . Even if it concerned both sequential and simultaneous FDG‐PET/MRI studies, Xiao et al showed in a recent meta‐analysis a pooled sensitivity of 91% to detect head and neck cancer . To strengthen our view, Schaarschmidt et al recently showed in a series, including a majority of small size lesions (10/12), a higher sensitivity of FDG‐PET/MRI (Se = 75%) than FDG‐PET/CT (sensitivity = 59%, P = .06) and MRI (sensitivity = 50%, P = .03) in detecting primary tumors …”
Section: Discussionmentioning
confidence: 75%
“…As far as our information goes, our meta-analysis is the first to assess the prognostic values of 18 F-FDG PET/CT parameters in NPC patients. Of the remaining studies on head and neck cancers, 14 studies analysed the diagnostic performance of PET for NPC [5759], and distant metastasis [6067], residual or recurrent disease [6870] for head and neck cancers; 4 studies evaluated PET parameters for EFS, OS, disease-free survival (DFS) or loco-regional control using HRs, odds radios or risk radios [47, 7173]. Pak.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer is supposedly one field in which PET/MRI might offer benefits over PET/CT, particularly with regard to local tumor invasion. Several studies showed that PET/MRI equals PET/CT in characterizing tumors and lymph nodes . However, specific data about the imaging assessment of local tumor resectability with PET/MR are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that PET/MRI equals PET/CT in characterizing tumors and lymph nodes. [11][12][13][14][15][16][17][18] However, specific data about the imaging assessment of local tumor resectability with PET/ MR are currently lacking.…”
mentioning
confidence: 99%